Integration of Health Law and Radiation Safety Aspects in the Medical Physics Curriculum for Radiotherapy Treatment - Widyaningrum, Ratna; Nofik, Khoirun; Masruroh, Ainul; Hernawati, Sari (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the legal regulations related to radiation safety in radiotherapy and develop a systematic approach to integrating health law and radiation safety aspects into the medical physics curriculum. Methodology: A qualitative library research approach was used, analyzing journals, regulatory documents (WHO, IAEA, BAPETEN), and academic books through content analysis. Main Findings: International and national regulations, including IAEA, ICRP, and BAPETEN, strictly govern radiation safety in radiotherapy, covering dose limits, exposure monitoring, and waste management. However, medical physics curricula lack structured integration of legal and safety aspects. A systematic curriculum model is proposed, incorporating progressive learning, practical simulations, clinical internships, and competency-based assessments to enhance student preparedness in radiation protection and regulatory compliance. Novelty/Originality of this study: This study proposes a structured curriculum model linking technical and regulatory aspects through progressive learning, practical training, and industry collaboration, ensuring better radiation safety implementation in clinical practice.